Bomarzo: The Banning (Revista Argentina de Musicología, 2003)
Premiered in Washington with great success in May 1967, Bomarzo, the opera by Argentine composer Alberto Ginastera to a libretto by Manuel Mujica Láinez, awaited its Argentinian premiere in Buenos Aires in August of that year. However, an unexpected ban issued by the city government prevented the premiere, in an act of censorship that is still strongly remembered and which is actualized by the performance of the opera in the Teatro Colón's current opera season. The measures then taken and their wording make it explicit the official position of the government; however, other "stories" can be seen through it: the whim that was understood as authority, a society willing to accept censorship as the government's responsibility and a conception of truth -eternal and unique- that would lead to authoritarianism.